Metazoans of redoxcline sediments in Mediterranean deep-sea hypersaline anoxic basins. Issue 1 (December 2015) - Bernhard, Joan; Morrison, Colin; Pape, Ellen; Beaudoin, David; Todaro, M.; Pachiadaki, Maria; Kormas, Konstantinos; Edgcomb, Virginia
Abstract Background The deep-sea hypersaline anoxic basins (DHABs) of the Mediterranean (water depth 3500 m) are some of the most extreme oceanic habitats known. Brines of DHABs are nearly saturated with salt, leading many to suspect they are uninhabitable for eukaryotes. While diverse bacterial and protistan communities are reported from some DHAB haloclines and brines, loriciferans are the only metazoan reported to inhabit the anoxic DHAB brines. Our goal was to further investigate metazoan communities in DHAB haloclines and brines. Results We report observations from sediments of three DHAB (Urania, Discovery, L'Atalante) haloclines, comparing these to observations from sediments underlying normoxic waters of typical Mediterranean salinity. Due to technical difficulties, sampling of the brines was not possible. Morphotype analysis indicates nematodes are the most abundant taxon; crustaceans, loriciferans and bryozoans were also noted. Among nematodes, Daptonema was the most abundant genus; three morphotypes were noted with a degree of endemicity. The majority of rRNA sequences were from planktonic taxa, suggesting that at least some individual metazoans were preserved and inactive. Nematode abundance data, in some cases determined from direct counts of sediments incubated in situ with CellTrackerTM Green, was patchy but generally indicates the highest abundances in either normoxic control samples or in upper halocline samples; nematodes were absent or very rare in lower halocline samples. Ultrastructural analysis indicates the nematodes in L'Atalante normoxic control sediments were fit, while specimens from L'Atalante upper halocline were healthy or had only recently died and those from the lower halocline had no identifiable organelles. Loriciferans, which were only rarely encountered, were found in both normoxic control samples as well as in Discovery and L'Atalante haloclines. It is not clear how a metazoan taxon could remain viable under this wide range of conditions. Conclusions We document a community of living nematodes in normoxic, normal saline deep-sea Mediterranean sediments and in the upper halocline portions of the DHABs. Occurrences of nematodes in mid-halocline and lower halocline samples did not provide compelling evidence of a living community in those zones. The possibility of a viable metazoan community in brines of DHABs is not supported by our data at this time.